Repercussions of paternity in teenager's life - Ana Luisa Almeida Melo; Maria de Fátima Antero Sousa Machado; Evanira Rodrigues Maia; Karla Jimena Araújo de Jesus Sampaio (Universidade Federal do Ceará, 2012)
The aim of this study is to analyze the adolescents' perception on early paternity, understanding the process of coping and the changes occurred. A qualitative study carried out in Crato-CE, Brazil, in 2009, with ten fathers that experienced paternity in adolescence, identified through the "snow ball" technique. For data collection semi-structured interviews were used, from September to October. Data were organized through the technique of Collective Subjects Discourse. For the adolescents, the experience was considered positive spite the difficulties, responsibilities and changes in social life. Family support was shown to be favorable to coping and interrupting education had a negative impact in adolescents' life. We suggest further studies to promote public policies and systematized actions to face this problem, focusing on prevention, assuming paternal responsibilities, in addition to financial strategies and early participation in the job market.